Phase Evolution of CuS System in Ethylene Glycol Solution: the Effect of Anion and PVP on the Transformation of Thiourea. Issue 8 (19th July 2013) - Fang, Zhen; Wang, Chenyan; Fan, Fan; Hao, Shenghua; Long, Liuyang; Song, Yixuan; Qiang, Tingting
Abstract The transformation mechanisms of thiourea in ethylene glycol solution was systematically investigated in this report, which shows the transformation process is influenced by the anion (NO3−, Cl−, Br−) and polyvinylpyrrolidone (PVP). Thiourea (tu) isomerizes into ammonium thiocyanate when NO3− is present, regardless of the existence of PVP. For Cl−, thiourea coordinates with copper anion to form [Cu(tu)]Cl·1/2H2O complex whether PVP is present. When it comes to Br−, thiourea hydrolyzes in the cooperation of PVP or coordinates with copper anion to form [Cu(tu)Br]·1/2H2O complex without PVP. The different transformation routes will lead to different phase evolution of the CuS system. This work may provide a new understanding of the transformation of thiourea in ethylene glycol solution. The optical properties of the as‐prepared copper sulfides exhibit signi?cant stoichiometry‐dependent features which may have potential applications in semiconductor photovoltaic devices.